Hybrid PET/CT and SPECT/CT Imaging A Teaching File - Delbeke, Dominique; Israel, Ora.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Hybrid PET/CT and SPECT/CT Imaging: A Teaching File presents a complete book on state-of-the-art integrated PET/CT and SPECT/CT imaging systems. Edited by Drs. Dominique Delbeke and Ora Israel, this practical guide includes in-depth cases that will advance the skills of nuclear physicians and radiologists while also preparing residents for the field of nuclear medicine and radiology. Internationally-recognized contributors provide the reader with chapters covering the technical and clinical aspects of hybrid imaging, including basic principles, physics and instrumentation, the normal distribution of radiopharmaceuticals, and protocols critical to the field. A comprehensive review of nuclear oncology cases found in everyday practice are addressed, including among other clinical applications head and neck tumors, breast cancer, lung neoplasms, colorectal cancer, pancreatic cancer, and genitourinary tumors. Additional chapters examine the use of these modalities in pediatric patients, benign bone diseases and infection, and cardiac hybrid imaging. A wealth of illustrations reinforces the key teaching points discussed throughout the book.
General -- History and Principles of Hybrid Imaging -- Normal Distribution, Variants, Pitfalls, and Artifacts -- Clinical Applications in Oncology -- Tumors of the Central Nervous System -- Hybrid Imaging of Head and Neck Malignancies -- Lung Cancer -- Breast Cancer -- Colorectal Cancer -- 18F-FDG PET/CT in Tumors of the Gastrointestinal Tract: Esophageal and Gastric Cancer and Gastrointestinal Stromal Tumors (GIST) -- Hepatobiliary and Pancreatic Malignancies -- Gynecological Tumors -- Hybrid Imaging in Malignancies of the Urinary Tract, Prostate, and Testicular Cancers -- Thyroid Cancer -- Endocrine Tumors -- Lymphoma -- Melanoma -- Malignancy of the Bone: Primary Tumors, Lymphoma, and Skeletal Metastases -- Pediatric Applications for PET/CT and SPECT/CT -- Other Clinical Applications -- Cardiac Hybrid Imaging (PET/CT and SPECT/CT): Assessment of CAD -- Hybrid Imaging of Benign Skeletal Diseases -- Infectious and Inflammatory Diseases.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Nuclear Medicine